Experimental Assessment of Integrated Technology Application Used to Rain (WM4RR) & Floods Reduction (AR-DWIS) in Jakarta. (2015) - Goenawan, Raden Djoko; Ridwan, Ridwan; Sadly, Muhammad; Sudinda, Teddy; Kudsy, Mahally; Seto, Tri Handoko; Harsoyo, Budi
Abstract: Flood has always been a problem in Indonesia since the colonization era. First flood occurred on January 10 th, 1932 on Sabang Street. After Indonesian independence in 1945, significant flood events occurred in 1979 and 2007 has caused 4.3 Trillion IDR (T) economic losses and killed 80 persons), 2013 (20 T), 2014 (12 T), and the latest flood event on 9-10 February 2015 had caused a total loss of 10 T IDR (1$=13, 000 IDR). The provincial rules in Jakarta Number 20/2013 stated that the 4% of land covered by building must compensate with 4% holes volume on that area. However, the data shown that ±30% of Jakarta's land surface is located under sea level and most building in Jakarta is not follow those rules. Furthermore, the capacity of all drainage in Jakarta has lower capacity than required and only 30% of that drainage working properly. Nowadays, the open green land of Jakarta is only 9.9% with 1.9% change-land use rate per year. Government of Jakarta has policy mentions that every deep-well exploitations must registered with water tax. To anticipate future floods, BPPT has a flood solution concept by combining two activities, for example rain reduction (Weather Modification for Rain Reduction, WM-4-RR; Seto et. al., 2011), and flood reduction with Artificial Recharge Deep Well Injection System (AR-DWIS; Sudinda et.al., 2006-2009), and technology innovation such as WM-RR & AR-DWIS (Goenawan et.al., 2014). The WM-4-RR & AR-DWIS have proven to be able to reduce flood approximately to 33% as stated by Mohajit et.al. (2014). It was assumed that flood peak in Jakarta is equivalent to 800 m 3 /s, therefore Jakarta needs until 2000 AR-DWIS in which each capacity is 400 l/s. While, BPPT and Ristek's building has made experiment & development for AR-DWIS (BR-1) since 2006, the capacity is still 1.43 l/s or 85.71 l/minute or 2.057 m 3 /hour.